Topological phenomena at defects in acoustic, photonic and solid-state lattices - Lin, Zhi-Kang (2023)
There are two prominent applications of the mathematical concept of topology to the physics of materials: band topology, which classifies different topological insulators and semimetals, and topological defects that represent immutable deviations of a solid lattice from its ideal crystalline form. Although these two classes of topological phenomena have generally been treated separately, recent experimental advancements have begun to probe their intricate and surprising interactions, in solid-state materials as well as in metamaterials. Topological lattice defects in topological materials offer a platform to explore a diverse range of phenomena, such as robust topological-bound states, fractional charges, topological Wannier cycles, chiral and gravitational anomalies, topological lasers and topological-defect-induced pumping and non-Hermitian skin effects. In this Perspective article, we survey the developments in this rapidly moving field from both theoretical and experimental perspectives, with an emphasis on the latter. We also give an outlook on the potential impact of these phenomena on condensed matter physics, photonics, acoustics and materials science.